LACUNA-RELATED PHENOMENA IN A CULTURAL CONTEXT (Scientific journal of the Fergana State University, 2024)
This article discusses aspects of the lacuna, which is one of the phenomena formed by comparing the lexical layers of languages, which are different from reality in the linguistic and cultural context. Also, it is noted that in the scientific landscape of the world, as any thing and reality develops from the harmony of existence-space, in linguistics, especially at the lexical level, there are also spaces that need to be filled. The differences between the phenomena of equivalence, lacuna and reality are explained with the help of examples.